Constipations in elderly: diagnostics and treatment approach - Yu. O. Shulpekova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2011)
The aim of review. To illuminate principal causes and features of manifestations of constipation at elderly patients, to present a general investigation and treat- ment plan.Original positions. In economically developed countries about one third of population over 65 years of age has constipation. One of the vital issues related to it, is decrease of quality of life and social activity of patients. The basic role in intestinal function disorders is played not so much by age-related changes of gastro-intestinal tract, but rather by systemic back- ground disease, characteristic for persons of the senior age. In some cases functional constipation is present. At investigation of the patient it is especially important to estimate history of drug intake, to pay the special attention to signs of obscure depression and anxiety, systemic and neurologic diseases and so- called «red flags». Constipation with delayed transit and megarectum are associated to the risk of fecal impaction, compression of urinary tract and stercoral colitis development, with intestinal perforation, blee- ding and suppuration.At treatment prescription it is necessary to take into account nature of constipation, features of clini- cal pattern, intestinal transit, incidental or persistent course. Adequate nutrition, physical motions, treat- ment of cognitive disorders and care for the patient have major value. Algorithms of stage-by-stage treat- ment of constipation with normal and delayed transit are presented.Conclusion. Disorder of emptying of intestine in elderly age is a common problem which can significantly aggravate general state of the patient and sometimes result in lethal complications. Medical staff should pay special attention to evaluation of intestinal functions and comprehend stage-by-stage constipation treatment.